Humanitarian and Weapons of Mass Destruction International Humanitarian Law - Ali, Tahani Ahmed (Journal of Economic, Administrative and Legal Sciences, 2024)
The present study investigates the humanitarian consequences of the spread of weapons of mass destruction (WMDs). The proliferation of weapons of mass destruction (WMDs) is a significant apprehension on a global scale, as both state and non-state entities endeavor to obtain them. Despite the concerted efforts of developed nations and international organizations, including the United Nations and the International Atomic Energy Agency, the task of managing proliferation has proven to be a challenging one. The present essay delves into the perils associated with the utilization of these armaments on human existence, the ramifications on economic progress, and approaches to avert their proliferation. The regulation of warfare has been increasingly pursued by states and civil societies through the adoption of humanitarian disarmament as a strategy. The humanitarian perspective has been significantly enhanced by multilateral agreements pertaining to the regulation of conventional weapons, such as the 1980 Convention on Certain Conventional Weapons and the 1997 Anti-Personnel Landmine Convention. The article culminates by proposing recommendations to enhance the effectiveness of arms control agreements, advance disarmament efforts, establish novel legal frameworks at the global level, and prioritize non-state entities as potential sources of weapons of mass destruction.
Keywords: Weapons of Mass Destruction (WMDs); Proliferation; Humanitarian approach; International law regulations; Biological and Toxin Weapons Conventions